Pentamerism and modularity in sea urchins - López-Sauceda, Juan; Aragón, José Luis (TIP Revista Especializada en Ciencias Químico-Biológicas, 2013)
Fivefold symmetry is important in many scientific areas. In particular, five-part units or pentamerism is a basic pattern in the design of many animals and plants. Despite some efforts, a definite explanation of the abundance of this pentamerism is still missing. In this note we use sea urchins as working examples to propose some ideas, based on spatial efficiency arguments and the concept of modular systems, which can give clues to understand the advantages of a pentameral body plan partition in biological systems.